Basics of sociology of education: a collection of current research areas and theories - book review - Fináncz, Judit (Autonomy and Responsibility Journal of Educational Sciences, 2022)
Book: Varga Aranka, (Ed.) (2015): A nevelésszociológia alapjai. Pécsi Tudományegyetem Bölcsészettudományi Kar Neveléstudományi Intézet Romológia és Nevelésszociológia Tanszék, Wlislocki Henrik Szakkollégium, Pécs.